AB1218 Anakinra and canakinumab in children suffering from systemic onset juvenile idiopathic arthritis, from cryopyrin associated fever syndromes or from recurrences of pericardial effusion. (23rd January 2014) - Emminger, W.; Dufek, S.; Perneczky-Hintringer, E.; Luckner, D.; Fodor, S.; Ulbrich, A.
Abstract : Background: The blockade of interleukin 1 has been shown to reduce the corticosteroid (CS) dependence in children suffering from systemic onset juvenile idiopathic arthritis (soJIA) and from cryopyrin-associated fever syndromes (CAPS). Methods: We show the clinical experiences in 9 pediatric patients, who were treated in a pediatric rheumatologic outpatient center. 6 children were suffering from soJIA, 2 from CAPS and one from recurrent episodes of pericardial effusion after stopping CS. Results: In January 2012, five of six children with soJIA are off steroids for 13, 17, 38, 43 and 53 months, respectively. The daily doses of anakinra ranged from 1 to 4 mg/kg. The sixth child suffered from soJIA with relapsing episodes of macrophage-activation syndrome. We observed a decrease in inflammatory parameters (ferritin, erythrocyte sedimentation rate, C-reactive protein and serum amyloid A), but the inflammatory disease was continuing and the girl developed lung failure due to the chronic inflammatory state of activated macrophages. Therapy was changed from anakinra, methotrexate and corticosteroids to cyclophosphamide, the interleukin-6 antibody tocilizumab and high doses of daily CS. With the latter therapy all inflammatory parameters returned to normal values. Two children are suffering from Muckle-Wells syndrome (MWS) and neonatal onset multiinflammatory disease (NOMID). Both children showed rapid clinical response to 1-2 mg/kg anakinra per day. The therapy was changed from anakinra to the interleukin 1β-antibody canakinumab, with continuing benefit. One adolescent experienced relapsing courses of pericardial effusion through 10 months whenever CS doses have been gradually reduced. CS could be reduced and stopped during concomitant Anakinra therapy. Conclusions: The observations in the presented nine children show that anakinra and canakinumab are effective therapy for many children suffering from soJIA, for those suffering from CAPS and may be effective therapy for some children suffering from non-infectious relapsing pericardial effusions. Disclosure of Interest: None Declared